Sincronización entre distintas cronologías del Noreste de la Península Ibérica - Génova R. (Jornadas sobre las bases ecológicas para la gestión en ecosistemas terrestres, 1989)
The degree of synchronisation between nine different chronologies located in three different zones of the Iberian Peninsula has been analysed. All the values obtained for both statistical tests used were significant. The average for the test of parallel agreement (gleichlaufigkeit) was 67.4 per cent. This value is higher than observed by other authors in other areas of Spain, and is closely related with that observed in the Central Alps and Scotland. The synchronisation is maintained over large distances (more than 350 kilometers). Results seem to indicate that high frequency variations in the tree-ring series could be related with precipitation more than with temperature.
Jornadas sobre las Bases Ecológicas para la Gestión en Ecosistemas Terrestres, 1988/06/13-15, Zaragoza (Spain)